Stress, Dietary Habits, and Their Relationship with Hypertension among the Elderly in Sukabumi, Indonesia: A Cross-Sectional Study - Teten Tresnawan (Journal of Health and Nutrition Research, 2025)
Hypertension in the elderly is a major health concern driven by modifiable factors such as stress and diet. Stress, a response to stressors that disrupt an individual’s ability to cope, has been linked to the onset of hypertension. Similarly, dietary patterns, which reflect the quality of food and beverages consumed, play a significant role in a person’s health and the development of hypertension. This study aims to explore the relationship between stress, diet, and hypertension incidence among the elderly in Sukabumi City and Regency. A cross‑sectional study of 339 adults aged 60–79 years was conducted in Sukabumi (cluster random sampling across health centres). Stress was measured with the Perceived Stress Scale, diet with a modified Food‑Frequency Questionnaire, and hypertension by blood‑pressure readings. Most participants were female (74 %) and unemployed (80 %); 81 % had only primary‑school education. Hypertension prevalence was 54 %. Moderate stress (53 %) and poor diet (55 %) predominated. Hypertension was significantly associated with both stress (χ² = 4.2, P < 0.001) and diet (χ² = 152.6, P < 0.001). Stress and poor dietary patterns are significantly associated with the incidence of hypertension among the elderly in Sukabumi. It is recommended that health centers enhance health promotion activities related to hypertension prevention for the elderly in the region.